2019
DOI: 10.3991/ijet.v14i20.10992
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Socialization on Collaborative Learning Method in E-Learning Management System (eLMS)

Abstract: The rapidly increasing use of information and communication technology (ICT) in the academic community allows learners to access information and academic content anywhere at anytime. e-Learning Management System (eLMS) is one of the popular tools that are increasingly being used in higher education institutions to support and manage teaching and learning. This empirical study was thus conducted to investigate the impact of e-learning on the socialisation among students in Iraq. The sample comprised of 109 unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…In this review, we found that the role of instructor was still irreplaceable, because the instructor's involvement existed in most of the AI-STEM research. Even though AI can free instructors from redundant tasks in STEM education, it still lacks the human ability to convey social emotion, solve critical problems, and implement creative activities (Collinson, 1996;Gary, 2019;Muhisn et al, 2019). Therefore, although AI techniques can bring opportunities to develop STEM education (Hwang et al, 2020), we cannot overstate the role of technology and overlook the essential role of instructor (Selwyn, 2016).…”
Section: Educational Implicationsmentioning
confidence: 99%
“…In this review, we found that the role of instructor was still irreplaceable, because the instructor's involvement existed in most of the AI-STEM research. Even though AI can free instructors from redundant tasks in STEM education, it still lacks the human ability to convey social emotion, solve critical problems, and implement creative activities (Collinson, 1996;Gary, 2019;Muhisn et al, 2019). Therefore, although AI techniques can bring opportunities to develop STEM education (Hwang et al, 2020), we cannot overstate the role of technology and overlook the essential role of instructor (Selwyn, 2016).…”
Section: Educational Implicationsmentioning
confidence: 99%
“…For much achievement data, association rules in data mining technology can be used to obtain the association relationship between subjects and find the neglected content in learning, which can provide targeted help and academic early warning for each student, and provide teaching guidance for teachers and administrators. Data mining is regarded as a set of technologies that allow automatic or semi-automatic extraction of much useful information, models and trends from many datasets, such as "clustering", "classification", "association" and "regression"; intelligent artificial algorithms such as Apriori algorithm, Bayesian algorithm, and neural network will be used to extract patterns from data, and these patterns are realized to interpret and predict their behaviors [4][5][6][7][8]. Association rule is an important task to discover frequent patterns in data mining.…”
Section: Introductionmentioning
confidence: 99%
“…Online learning provides a change in the world of Education that provides opportunities for students to receive and share information easily (El-Seoud, 2014). Using the internet is not only effective but also students are also faster to access various learning materials (Muhisn, 2019).…”
Section: Tabel 4 Comparison Of the N-gain Score Of The Learning Outcomesmentioning
confidence: 99%